2: ENVISIONING CREATIVE COLLABORATION BETWEEN FACULTY AND TECHNOLOGISTS. (10th October 2017) - Rathbun, Gail A.; Kuhlenschmidt, Sally; Sacks, David
Abstract : Faculty developers must often mediate conflicts resulting from differences between seemingly mutually exclusive cultures that university technologists and university teachers inhabit. Activity theory embraces workplace conflict as normal and as contributing to organizing health and adaptation, in contrast to a functionalist approach that focuses on how to maintain system equilibrium. Engeström's (1987) interpretation of activity theory provides a theoretically informed framework for understanding different forms of human activity, mediated by culturally molded rules, values, and division of labor, without suffering from the polarizing effects of an us‐versus‐them approach.